Mass media effects in formation of attitudes towards an internalized shopping center: The Conceptual understanding on the usefulness of advertising media - Izian Idris, *; Toh, Evelyn Bee Hwa * (Lifescience Global, 2020)
Retailing plays a major role in attracting tourists here and Malaysia is now known amongst the most popular shopping hubs in the world. Amongst the most iconic shopping centers that Malaysia is known for include KLCC, Pavilion, Midvalley Megamall, One Utama and Sunway Pyramid. According to Tourism Malaysia (2018), amongst the key attractions for tourists as well as Malaysians is the abundance of shopping centers available here. Most of these major shopping centres compete head to head in attracting more shoppers. It is established that in order for these iconic shopping centers to stand out in the minds of consumers, they depend heavily in creating the right retail atmosphere as well as a blend of advertising and promotions in enticing shoppers to patronage and shop there. Clow and Baack (2007) perceive there are many choices of advertising media. Effectively mixing these media is an important part of designing quality advertising. To do so, the advantages and disadvantages of each individual medium must be understood so that an advertising campaign features successful combinations. It also helps to know how attentive consumers are to various media. Apart from the functions of media on communicating what a shopping center has to offer, media works on creating a positive brand image for the shopping center. As such, this study seeks to establish if shopping centers are indeed using the appropriate blend of media in the formation of people attitudes towards the shopping center.